Ethnobotany of Taro Plant Diversity (Colocasia esculenta L. Schott) in Magelang City and Regency as a Biological Reference Book - Wakhidatunnisa, Yunika Nurma; Kusumaningrum, Serafica Btari Christiyani; Darmawan, Ericka; Wahyudiningsih, Tri Suwarni (Biosfer: Jurnal Pendidikan Biologi, 2025)
The diversity of taro plants in the Magelang area has been used for a long time by traditional communities from generation to generation. But knowledge related to the use of taro plants for purposes other than food is not widely known to the public. This study aims to determine the untilization of taro plants (Colocasia esculenta L. Schott) and analyze the feasibility of ethnobotanical reference books of taro plant diversity (Colocasia esculenta L. Schott) in Magelang City and Regency. This study is a type of mixed method research, which is a combination of ethnographic research methods with Research and Development (R&D) research. The results of ethnographic research are then used as a source of reading through the development of reference books. Development research was carried out using a 4-D research model and then limited to 3-D (define, design, and develop) due to time constraints. Based on the research that has been carried out, it is known that there are 5 varieties of taro plants (Colocasia esculenta L. Schott) that are found and used by the local people of Magelang, namely Taro Pratama 1, Pratama 2, Pratama 3, Taro Water/Bogor, and black Taro which are used by the community for various life purposes. The reference book based on the ethnobotanical study of taro plant diversity developed is suitable for use as a biological reference book with a percentage of 91% in material experts with excellent category, 83% in media experts with good category, and 95.89% in the results of community response tests with excellent category.